Orally Administrated Lactobacillus pentosus var. plantarum C29 Ameliorates Age-Dependent Colitis by Inhibiting the Nuclear Factor-Kappa B Signaling Pathway via the Regulation of Lipopolysaccharide Production by Gut Microbiota - Jeong, Jin-Ju (PLoS One, 2015)
To evaluate the anti-inflammaging effect of lactic acid bacteria (LAB) on age-dependent inflammation, we first screened and selected a tumor necrosis factor (TNF)-α and reactive oxygen species (ROS)-inhibitory LAB, Lactobacillus pentosus var. plantarum C29, among the LABs isolated from fermented vegetables using LPS-stimulated mouse peritoneal macrophages. Oral administration of C29 (2 × 10(9) CFU/rat) for 8 weeks in aged Fischer 344 rats (age, 16 months) inhibited the expression of the inflammatory markers myeloperoxidase, inducible nitric oxide (NO) synthase, cyclooxygenase-2, pro-inflammatory cytokines tumor necrosis factor (TNF)-α and IL-6 and the activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), activator protein 1 (AP1), and mitogen-activated protein kinases (MAPKs). Treatment with C29 induced the expression of tight junction proteins ZO-1, occludin, and claudin-1, and reduced intestinal microbial LPS and plasmatic LPS levels and ROS, as well as the Firmicutes to Bacteroidetes ratio, which is significantly higher in aged rats than in young rats. C29 treatment also reduced plasmatic reactive oxygen species, malondialdehyde, C-reactive protein, and TNF-α, and suppressed expression of senescence markers p16 and p53 in the colon of the aged rats, but increased SIRT 1 expression. Based on these findings, we concluded that C29 treatment may suppress aging-dependent colitis by inhibiting NF-κB, AP1, and MAPK activation via the inhibition of gut microbiota LPS production and the induction of tight junction protein expression.